2008
DOI: 10.1029/2007gl031962
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intraseasonal oscillation and diurnal variation of summer rainfall over the South China Sea

Abstract: [1] The diurnal variations in summer rainfall over the South China Sea (110°EÀ120°E, 10°NÀ20°N) are examined for active and inactive intraseasonal oscillation (ISO) periods that are characterized by strong and weak 850-hPa zonal winds, respectively. By analyzing the rainfall retrievals from the Tropical Rainfall Measuring Mission Precipitation Radar for the period 1999 -2006, it is found that the peak rainfall during the active and inactive ISO periods occurs in the late morning and late evening, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 13 publications
(28 reference statements)
2
37
0
Order By: Relevance
“…The organisation of convection into mesoscale convective systems is also a strong function of the time of day, especially over the ocean (Nesbitt and Zipser, 2003). The diurnal cycle is further complicated by interactions with intraseasonal variability such as the Madden-Julian Oscillation (MJO; Tian et al, 2006;Ichikawa and Yasunari, 2006Ho et al, 2008). Such scale interactions are an integral part of the convection, precipitation and circulation characteristics of the region (Sui and Lau, 1992;Mapes and Houze, 1993;Chen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The organisation of convection into mesoscale convective systems is also a strong function of the time of day, especially over the ocean (Nesbitt and Zipser, 2003). The diurnal cycle is further complicated by interactions with intraseasonal variability such as the Madden-Julian Oscillation (MJO; Tian et al, 2006;Ichikawa and Yasunari, 2006Ho et al, 2008). Such scale interactions are an integral part of the convection, precipitation and circulation characteristics of the region (Sui and Lau, 1992;Mapes and Houze, 1993;Chen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the diurnal cycle of rainfall in southeastern China and the South China Sea may be modulated greatly by the land and sea breeze, which is characterized by diurnal circulation with a rising (sinking) motion in the late afternoon over warm continents (adjacent to cool sea waters) and the reversed circulation during the early morning [16,17].…”
mentioning
confidence: 99%
“…Thus, the convective processes over the South China Sea would not be expected to be related to the TC formation process. Indeed, the diurnal evolution of convection throughout the morning and afternoon appears to correspond with the climatological diurnal variation of rainfall during a WWB as in Ho et al (2008). In the morning (0000 UTC, 0800 LT in Fig.…”
Section: A Diurnal Evolution Of Mcss During Formation (24-27 Septembmentioning
confidence: 99%
“…When the strong large-scale southwesterlies are present over the South China Sea owing to the eastward movement of the MJO over the western North Pacific (section 4), the primary area in which most of the MCSs and heavy precipitation originate is upstream and over the Philippines (Hoyos and Webster 2007;Ho et al 2008;Park et al 2011). Based on an analysis of eight years of TRMM PR rain rates, Ho et al (2008) found out that the diurnal maximum of rainfall during the WWB period occurs in the late morning.…”
Section: A Diurnal Evolution Of Mcss During Formation (24-27 Septembmentioning
confidence: 99%
See 1 more Smart Citation